The clinical value of iodine-125 seed implantation in the treatment of iodine-refractory differentiated thyroid carcinoma - Wan, Qin; Tan, Liling; Tang, Xinlan; Wang, Wenjun; Su, Yu; Wu, Zhen; Ke, Mengmeng; Chen, Zhijun (Frontiers in Endocrinology, 2024)
Objective: To explore the clinical benefits of 125I seed implantation for iodine-refractory differentiated thyroid cancer (RAIR-DTC). Methods A retrospective analysis was conducted on 36 patients with RAIR-DTC who underwent radioactive 125I seed implantation from January 2015 to February 2022, involving 73 lesions. Prescription dose: 80~120 Gy. All cases were followed up at 1, 3, and 5 months postoperatively to monitor changes in tumor size, serum thyroglobulin (Tg), and serum anti-thyroglobulin antibody levels in thyrotropin-inhibited states, pain scores, and postoperative adverse reactions. The data were processed and analyzed using IBM SPSS 26.0. LER (Local Effective Rate) and LCR (Local Control Rate) were expressed as n (%), tumor diameter, Tg, and pain scores were represented as Median (Q1, Q3). Pairwise comparisons were conducted using the Wilcoxon signed-rank test, and a p-value of less than 0.05 indicated statistical significance. Results Tumor size was significantly reduced after treatment (all P < 0.001): tumor length diameters were 32.67 (17.70, 45.72) mm, 27.45 (12.30, 39.98) mm, 20.70 (11.98, 37.58) mm, and 20.39 (10.56, 33.20) mm in the preoperative, 1-, 3-, and 5-months postoperative periods, respectively. Additionally, two consecutive post-treatment results were more minor than the previous results (P < 0.001). The LER at 1-, 3-, and 5-months post-surgery was 23.73%, 38.98%, and 52.54%, respectively, while the LCR at the same time points was 98.31%, 96.61%, and 94.92%, respectively. Patients' serum Tg levels decreased after surgery. (P < 0.001). Serum Tg levels were measured before surgery and 1-, 3-, and 5-months post-surgery. The results showed that serum Tg levels were 249.45 (79.39, 4718.75) ng/ml, 193.40 (44.53, 2829.00) ng/ml, 192.10 (25.58, 1758.00) ng/ml, and 136.25 (16.57, 1553.25) ng/ml, respectively. Two consecutive post-treatment results were more minor and statistically significant than the previous results (P < 0.001). The patients' pain symptoms were significantly relieved after 125I brachytherapy (P < 0.001). The pain scores before 125I seed implantation and at 1, 3, and 5 months after the operation were 5.00 (4.00, 6.00), 3.00 (2.25, 4.00), 2.00 (2.00, 3.00), and 2.00 (1.00, 3.00), respectively. Conclusion: Most lesions treated with 125I seed implantation in RAIR-DTC patients showed shrinkage and improved pain symptoms.